The Economic Policy Of Umar Bin Khattab To Face Ramadhan Crisis - zahra, Putri Sholihatuz; Herman, Sebastian (Islamic Economics and Business Review, 2023)
Abstract The Economic Crisis is a situation of instability that can affect individuals and even large groups that tend to harm. The threat of crisis did not only occur in the current era but in the Khulafaur Rashidun Era, namely during the time of Umar Bin Khattab, namely the Ramadan Crisis, which was a crisis that occurred in the Hijaz area and its surroundings between 17-18H. At that time Ramadan greatly impacted the economy of Muslims because the population was starving, the land was black, livestock died and prices soared. Even trading activities could not carry out their normal activities. Ramadah occurred because the rains did not fall which caused drought, the occurrence of the bubonic plague which disrupted trading activities and because of rampant adultery and judges who acted tyrannically. Umar bin Khattab radhiallahu anh made many changes to his policies at that time. The research method used in this study is qualitative research, using a historical approach in which the author collects written sources in this research. From the results of this writing, it can be interpreted that economic policy during the caliphate of Umar bin Khattab could not be separated from Umar's intelligence and expertise as a caliph with his ijtihad and deliberations he conducted with friends. It is hoped that this writing can provide references and guidelines for the implementation of governance in managing countries. Keywords: Umar bin Khattab, Ramadan, Economic Crisis, Islam